Vicia faba – Rhizobium leguminosarum system symbiotic relationship under stress of soil ph and aluminium - Bayoumi Hamuda, Hosam E.A.F.; Orosz, Erika; Hamuda, Yasmin; Tóth, Nikolett; Kecskés, Mihály (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
Aluminium (Al) toxicity is one of the most widespread agronomic problems in world. Selection of pH and Al tolerant strains of Rhizobium leguminosarum as well as Vicia faba was carried out in vitro and in vivo. Developing Al-tolerant faba bean cultivar is one approach to overcome this constraint. The growth of the strains was evaluated in term of optical density after 48 h incubation in rotary shaker at 28°C in broth defined basal medium. The investigation showed that Rhizobium strain Lóbab Z was the most tolerant strain to pH variations, while HB-3841str+ was the most sensitive one. Although the HB-3841str+ and E1012 strains were not able to grow at 25 μMKAl(SO4)2, but they grew at 25 μM Al(NO3)3. The results showed that the multiplication of Rhizobium strains (except E1012) was unaffected by 100 μM Al2(SO4)3, while the growth of the strains (except Bükköny 75/4) was affected by 50 μM AlCl3. The inhibitory increasing order of investigated Al compounds was found as following: Al(NO3)3 < Al2(SO4)3 < KAl(SO4)2 < AlCl3. From the above, it can be concluded that because of the ability of Rhizobium strain Lóbab Z to grow in vitro conditions containing high concentrations of Al, therefore we suggested using it as reference strain for nodulation potential in soil of high Al content. The effective strains were tested for their symbiotic performance with faba bean cultivar in clay loam brown forest soil with various pH values as well as with different Al doses. The best performance of all the strains was at 6.6 soil pH and between 50 and 100 Al mg kg-1 soil at pH was 5.31. The strains Bükköny 75/4 and HB-3841str+ were suitable for soils with a pH 6.6. While the strains Lóbab Z and Bükköny 75/4 were suitable for inoculating soil with pH 5.31 and soil containing Al levels between 50 and 100 mg kg-1 soil. The final conclusion is that the multiplication of the strains was dependent upon the Al ions and Bükköny 75/4 strain can be recommended for inoculating soil with pH 5.31 and containing Al levels between 50 and 100 mg kg-1 soil.
Keywords: Rhizobium leguminosarum; Soil pH and Al3 concentrations; Symbiotic relationship; Vicia faba